2016
DOI: 10.1038/srep26163
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high density optical data storage in common transparent plastics

Abstract: The ever-increasing demand for high data storage capacity has spurred research on development of innovative technologies and new storage materials. Conventional GByte optical discs (DVDs and Bluray) can be transformed into ultrahigh capacity storage media by encoding multi-level and multiplexed information within the three dimensional volume of a recording medium. However, in most cases the recording medium had to be photosensitive requiring doping with photochromic molecules or nanoparticles in a multilayer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Some other advanced multiplexing techniques have also been proposed, in order to obtain high capacity data storage within the same storage volume by using multi‐dimensional space, such as the third spatial coordinate, grayscale, multi‐spectrum, polarization, and so on . However, substantial improvements in these technologies are still needed to satisfy the requirements for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Some other advanced multiplexing techniques have also been proposed, in order to obtain high capacity data storage within the same storage volume by using multi‐dimensional space, such as the third spatial coordinate, grayscale, multi‐spectrum, polarization, and so on . However, substantial improvements in these technologies are still needed to satisfy the requirements for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric substrates comprising local mechanical stiffness pattern or nanostructural features are intensively investigated in the context of applications such as haptic displays (touchpads), stretchable electronics, mechanical and optical data storage devices, [1][2][3][4][5][6][7][8] or as instructive cell substrates guiding mechanosensitive (stem) cells. [9][10][11][12][13][14][15] While individual cells can react to structural features of few nanometers in size and mechanical differences in the Pascal (Pa) range, [9,14] the tactile sensitivity of a human finger is only capable of detecting structural features above 10 nm and local mechanics in the kPa regime.…”
Section: Introductionmentioning
confidence: 99%
“…We noted that besides the ionic liquid, the PMMA in 3D wire-hole array also plays a role as the gain medium. It has been reported that the irradiation by high-energy electrons or laser beams on PMMA results in fluorescent moieties [34] whose emission spectrum spans from 550 to 750 nm [35]. That's why two emission peaks remain observable (but not lasing) at 580 and 630 nm when removing the ionic liquid.…”
Section: Discussionmentioning
confidence: 99%